Effects of demand, manufacturing flexibility, cost and supply chain on product modularity: a study in Malaysia - Raihani Binti Zainol, N.; Al- Mamun, A.; Yukhthamarani Permarupan, P. (Canadian Center of Science and Education, 2013)
The objective of this study was to investigate the effect of customer demand, manufacturing flexibility, cost, and supply chain on product modularity. This study employed a cross-sectional design and a proportionate random sampling procedure was used to select 150 manufacturers from a list of 250 manufacturing companies in Malaysia, which are registered in Federation of Malaysian Manufacturers (FMM) and Association of Proton vendors. Data was collected from the middle and top management from these selected manufacturing organizations. Findings of this study noted that customer demand, manufacturing flexibility and supply chain has a significant positive effect on product modularity, whereas cost has a negative association with product modularity. Manufacturers, therefore, need to develop customer demand, manufacturing flexibility, cost, and supply chains to ensure the success in developing modularity product manufacturing. This study shows strong association for customer demand, manufacturing flexibility, cost, and supply chain to develop modularity product manufacturing